Analisa Spasial Lokasi Tempat Pembuangan Sampah Berbasis Web - Afifah; Mardhiah Fadhli (ABEC Indonesia, 2021)
One of the areas of facilities and infrastructure that needs to be considered in an area is the field of cleanliness. Waste Disposal Sites (TPS) are facilities that must be owned by every region in Indonesia. A good waste disposal site (TPS) must be fulfilled if the local government wants to tackle the waste problem in its area, therefore the waste disposal site must be established with established procedures and criteria such as distances between settlements, rivers, and roads, as well as no TPS. may interfere with existing facilities in accordance with what was said by Mr. Nofan as section of the TPA and TPS Management Section of the Pekanbaru City DLHK Office. Therefore, the Spatial Analysis of the Location of the Web-Based Disposal Site can assist the DLHK in finding new TPS locations as well as providing geographic information on existing TPS locations. This system is designed using framework CodeIgniter, PHP and MySQL programming languages as the DBMS, and ArcGIS as tools for analysis. After testing by the black box and user acceptance test, it can be concluded that the functionality of the system has succeeded as expected. With this system, the DLHK found it very helpful in determining the new TPS location, this system made their work more effective and efficient. For usability testing carried out with 65 people, the results obtained are 87.5% of users strongly agree. An easy-to-use system, an attractive appearance, and quick information that helps the community determine the location of a new TPS in their place, has made the community agree with this system.